Ansiedad y rendimiento académico en estudiantes de psicología de una Institución Superior de Riohacha-La Guajira - Palmezano Diaz, Andrea Paola; Palmezano Diaz, Vanessa Stefany (Universidad Antonio Nariño, 2024)
The objective of this research was to describe the relationship between anxiety and academic performance in students of the psychology program of a Higher Education Institution of the municipality of Riohacha- La Guajira. The methodology was of a descriptive correlational type, with a quantitative approach and non-experimental design; the sample consisted of 83 students of the psychology program of the mentioned Institution, for the collection of information the Anxiety Inventory: Trait-State (IDARE) was used, which is validated in Latin America.